TINGKAT KESIAPAN GENERASI EMAS INDONESIA DI ERA DISRUPSI BERDASARKAN KARAKTERISTIK DIGITAL NATIVE - Hadjaratie, Lillyan; Hasdiana, Hasdiana; Masaong, Abd Kadim; Panai, Abdul Haris (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This study aims to measure the level of student generation Z with Digital Native characteristics, which are limited to active students in Odd Semester 2022/2023 Information Technology Education Study Program (ITE) and Visual Arts Education Study Program (VAE) Faculty of Engineering, State University of Gorontalo, who will reach the age of 40 to 45 years in 2045 (Golden Generation). The research method used is descriptive quantitative. The results showed that ITE and VAE Study Program students were at a "moderate" level of readiness in welcoming Indonesia Gold 2045. The most dominant Digital Native characteristics possessed by ITE and VAE students were connected (always connected to friends because of technology and the internet) and digital literate, but tend not to understand clearly what is the goal in his life (goal-oriented). The conclusion that can be drawn is that ITE Study Program students are at a "High" level of readiness, compared to VAE Study Program students who are at a "Medium" level of readiness in welcoming Indonesia Gold 2045 based on digital native characteristics.